English Teacher’s Role in Forming the Students’ Discipline Character in Kurikulum Merdeka at SMP Negeri 3 Bawolato - Masirida Giawa; Trisman Harefa; Yasminar Amaerita Telaumbanua; Adieli Laoli (Universitas Sintuwu Maroso, 2025)
This research explores the role of English teachers in forming students’ discipline character in the context of Kurikulum Merdeka at SMP Negeri 3 Bawolato. Using a qualitative descriptive approach, the research investigates the causes of student indiscipline and how teachers respond to it through observation and interviews. Findings show that lack of parental supervision, peer influence, low motivation, and poor study habits are major contributing factors. The English teacher plays three roles: role model, classroom manager, and motivator. This research emphasizes the importance of character-based education in supporting curriculum implementation and student development.